From Pandemic Control to Data-Driven Governance: The Case of China’s Health Code - Cong, Wanshu (Frontiers in Political Science, 2021)
Current debates over digital contact tracing mainly focus on the tools and experiences in the West. China’s health code, while often seen as one of the earliest and most widely adopted apps since the outbreak of COVID-19, has not been studied specifically. This article provides a detailed analysis of the health code, draws comparison with the contact tracing apps developed by Google and Apple, and seeks to understand the specifications and contradictions internal to the health code’s development and deployment in China. Looking at both technical features and the mode and process of its adoption, the article argues that the health code is strictly speaking not a contact tracing tool, but a technology of population control which is integrated in traditional forms of control and facilitates the enhancement of such control. As a technology of ruling the population, rather than the virus as such, the health code also reveals crucial problems in the modernization and informatization of the state governance and public administration. A critique on the health code solely informed by privacy and personal data protection runs the risk of being co-opted by the government and technology companies deploying such tools to expand their surveillance and regulatory power.